Correction: Regional planning, land-use management, and governance in german metropolitan regions: the case of Rhine-Neckar metropolitan region - Yan, Simin; Growe, Anna (Land, 2024)
German cities and their hinterlands have a long tradition of cooperation; however, there remains considerable challenges when developing integrated governance models, especially in those metropolitan regions that cross state-boundaries. The Rhine-Neckar Metropolitan Region (MRN), with its unique location of a tri-state intersection, explored ways out of the governing dilemma and has pioneered cooperative federalism in Germany. To determine how the cross-jurisdictional cooperation is organized and realized in the MRN, and how well this model has worked in terms of regional planning, attributing land resources, and the reality of long-term governance, a series of interviews with involved officials and planners and MAXQDA software were employed to decode the transcribed text content. A second-hand qualitative database, including, but not limited to, meeting memos, protocols, and published works were added to examine our findings. The results indicated that diversified actors, a combined instrument, multiple collaborative contents, and the networked joint decision-making structure have strengthened the governance of the MRN. However, their public association-centered structure raised concerns in terms of inadequate participation of private agents and an excessive pursuit of regional balance as well. Ultimately, this paper discusses the inefficiency challenges facing the MRN and further reflects on the need for, and impacts of, high-level government participation in constituting a regional identity.
Gesehen am 19.01.2023